(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2023)
This article discusses important aspects of improving the legal framework of departmental lawmaking. The authors explore the current challenges and problems associated with the process of legal regulation within organizations and departments, and propose a number of solutions to improve this practice. The focus is on the efficiency, transparency and consistency of departmental regulations.